Nucleocytoplasmic transport of intrinsically disordered proteins studied by high‐speed super‐resolution microscopy. (3rd March 2020) - Junod, Samuel L.; Kelich, Joseph M.; Ma, Jiong; Yang, Weidong
Abstract: Both natively folded and intrinsically disordered proteins (IDPs) destined for the nucleus need to transport through the nuclear pore complexes (NPCs) in eukaryotic cells. NPCs allow for passive diffusion of small folded proteins while barricading large ones, unless they are facilitated by nuclear transport receptors. However, whether nucleocytoplasmic transport of IDPs would follow these rules remains unknown. By using a high‐speed super‐resolution fluorescence microscopy, we have measured transport kinetics and 3D spatial locations of transport routes through native NPCs for various IDPs. Our data revealed that the rules executed for folded proteins are not well followed by the IDPs. Instead, both large and small IDPs can passively diffuse through the NPCs. Furthermore, their diffusion efficiencies and routes are differentiated by their content ratio of charged (Ch) and hydrophobic (Hy) amino acids. A Ch/Hy‐ratio mechanism was finally suggested for nucleocytoplasmic transport of IDPs.